Development and Validation of a Method for the Quantification of an Alkaloid Fraction of Himatanthus lancifolius (Muell. Arg.) Woodson by Ultraviolet Spectroscopy - Patrícia M. S. S. Barros; Nádia M. G. de Couto; Andressa S. B. Silva; Wagner L. R. Barbosa (Journal of Chemistry)
For the registration of phytomedicines and their availability to the population, National Agency of Sanitary Surveillance (ANVISA) establishes quality, security, and efficacy parameters, stipulating control requirements similar to those applied to synthetic medicines. This work reports the investigation of the bark of Himatanthus lancifolius and its extracts aiming to contribute to the standardization of derivatives of this plant species. The developed quantification method shows high selectivity at 281nm, which confers confidence to the detection of the alkaloids. The method is robust, according to the current regulation, and shows linearity, precision, and accuracy, beside accessibility and simplicity in execute. The pH 10 alkaloid fraction obtained from the aqueous extract of the analyzed sample represents 0.219% in the dried extract. These results contribute for reducing the lack of methods for the quality control of phytomedicines prepared from H. lancifolius.